"Lies build trust": Social capital, masculinity, and community-based resource management in a Mexican fishery. (November 2019) - Siegelman, Ben; Haenn, Nora; Basurto, Xavier
Highlights: Fishermen use lies and ruse to bond, complicating notions of trust in CBNRM and favoring critical theories of social capital. Joking deceptions help men draw social boundaries and maintain harmony amidst competition for natural resources. Analysis of gendered social capital and masculinity reveals norms that shape resistance to externally-driven conservation. Social capital accrual and networks of trust can vary with differing resource pools, even among the same group of users. Abstract: This paper relates how fishermen in San Evaristo on Mexico's Baja peninsula employ fabrications to strengthen bonds of trust and navigate the complexities of common pool resource extraction. We argue this trickery complicates notions of social capital in community-based natural resource management, which emphasize communitarianism in the form of trust. Trust, defined as a mutual dependability often rooted in honesty, reliable information, or shared expectations, has long been recognized as essential to common pool resource management. Despite this, research that takes a critical approach to social capital places attention on the activities that foster social networks and their norms by arguing that social capital is a process. A critical approach illuminates San Evaristeño practices of lying and joking across social settings and contextualizes these practices within cultural values of harmony. As San Evaristeños assert somewhat paradoxically, for them "lies build trust." Importantly, a critical approach to this case study forces consideration of gender, an overlooked topic in social capital research. San Evaristeña women are excluded from the verbal jousting through which men maintain ties supporting their primacy in fishery management. Both men's joke-telling and San Evaristeños' aversion to conflict have implications for conservation outcomes. As a result, we use these findings to help explain local resistance to outsiders and external management strategies including land trusts, fishing cooperatives, and marine protected areas.